(untitled) (Web of Teachers: Inderscience Research, 2025)
This paper explores the most frequent grammatical errors made by beginner learners of the Japanese language and analyzes these errors through a pedagogical lens. Drawing from second language acquisition (SLA) theories, interlanguage development, and contrastive analysis, the study identifies common mistakes such as incorrect particle usage, misapplication of verb conjugations, confusion between formal and informal speech forms, and structural interference from the learners’ native languages. The research emphasizes how these errors reflect predictable developmental patterns and the challenges specific to learning Japanese grammar, which is notably different from Indo-European languages in terms of syntax, morphology, and honorifics. Based on classroom observations, learner data, and prior studies, the paper proposes targeted instructional strategies to reduce such errors. These include error-aware teaching methods, scaffolded input, and learner-centered corrective feedback. Moreover, the study highlights the importance of fostering grammatical awareness and utilizing technological tools such as digital platforms and corpus-based materials to enhance grammatical accuracy. Ultimately, this research aims to support Japanese language educators in developing more effective grammar-focused teaching approaches that align with the cognitive and linguistic needs of beginners.